Participatory Monitoring and Feedback System: An Important Entry Towards Sustainable Aquaculture in Bolinao, Northern Philippines - Verceles, Lailany; Talaue-McManus, Liana; Aliño, Porfirio (Science Diliman: A Journal of Pure and Applied Sciences; Vol 12 No 2 (2000), 2007)
The aquaculture industry in Caquiputan Channel contributed P2.3M to municipal revenues in 1998. However, the uncontrolled construction of fish pens and fish cages have contributed to the deterioration of the water quality in the Caquiputan Channel. Despite monitoring of parameters (e.g. DO, salinity, and temperature), low production was implicated because of limited dissolved oxygen supply. A participatory monitoring of fish pens and fish cages was facilitated to pave the way for sustainable aquaculture. A system for monitoring and disseminating information on water quality, production and zonation of pens and cages, has been pursued to assess the situation and identify mechanisms to regulate aquaculture activities. The feedback system adopted has raised and facilitated environmental awareness, issue identification, and implementation, of solutions to some major issues. Furthermore, the results have resulted in policy reforms, as embodied in the provisions on aquaculture in the Municipal Fisheries Ordinance.
Keywords: participatory monitoring; fishpens and fishcages; Caquiputan Channel